2006
DOI: 10.1196/annals.1317.076
|View full text |Cite
|
Sign up to set email alerts
|

Complexing Receptor Pharmacology

Abstract: The most well-characterized subgroup of family B G protein-coupledreceptors (GPCRs) comprises receptors for peptide hormones, such as secretin, calcitonin (CT), glucagon, and vasoactive intestinal peptide (VIP). Recent data suggest that many of these receptors can interact with a novel family of GPCR accessory proteins termed receptor activity modifying proteins (RAMPs). RAMP interaction with receptors can lead to a variety of actions that include chaperoning of the receptor protein to the cell surface as is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 44 publications
0
65
0
Order By: Relevance
“…Peptides of this family also share a unique mechanism of G-protein coupled receptor signaling by a novel class of single transmembrane proteins called receptor activity modifying proteins (RAMPs). RAMPs were first identified through their association with the calcitonin receptor-like receptor (CLR) and can interact with many other class II GPCRs to determine receptor ligand binding specificity [27]. In the case of CLR, association with RAMP1 produces a CGRP receptor, while association with RAMP2 or RAMP3 produces a receptor specific for AM.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides of this family also share a unique mechanism of G-protein coupled receptor signaling by a novel class of single transmembrane proteins called receptor activity modifying proteins (RAMPs). RAMPs were first identified through their association with the calcitonin receptor-like receptor (CLR) and can interact with many other class II GPCRs to determine receptor ligand binding specificity [27]. In the case of CLR, association with RAMP1 produces a CGRP receptor, while association with RAMP2 or RAMP3 produces a receptor specific for AM.…”
Section: Introductionmentioning
confidence: 99%
“…The GABA B1 receptor contains an endoplasmic reticulum retention signal in its cytoplasmic tail and must form a heterodimer with a GABA B2 receptor before the GABA B receptor can move to the cell surface (4). Receptor activity modifying proteins (RAMPs) facilitate trafficking and alter the ligand specificity of several class B GPCRs (5). MRAP is expressed in the adrenal cortex but is not found in commonly used model cells such as HEK293, COS, and CHO, and the MC2 receptor is not active when it is expressed in cells lacking MRAP.…”
mentioning
confidence: 99%
“…RAMP1 or MRAP. RAMP1 served as a negative control; it is a single transmembrane domain accessory protein for the calcitonin receptor-like receptor (5). When MC2 receptor was expressed with RAMP1 ( Fig.…”
mentioning
confidence: 99%
“…In particular, RAMP heterodimerization with calcitonin receptors is required for the formation of amylin receptors [58] [59] . More recent work has revealed that the RAMPs may modulate other functions such as receptor internalization and recycling and also the strength of activation of downstream signaling pathways [60] . Further studies, including conditional gene targeting models, which enable the spatial and temporal modulation of RAMP gene expression, are needed to elucidate the more detailed pathophysiological roles of the RAMP system.…”
Section: Discussionmentioning
confidence: 99%